Tax evasion, information reporting, and the regressive bias hypothesis - Simon Halphen Boserup; Jori Veng Pinje (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
A robust prediction from the tax evasion literature is that optimal auditing induces a regressive bias in effective tax rates compared to statutory rates. If correct, this will have important distributional consequences. Nevertheless, the regressive bias hypothesis has never been tested empirically. Using a unique data set, we provide evidence in favor of the regressive bias prediction but only when controlling for the tax agency's use of third-party information in predicting true incomes. In aggregate data, the regressive bias vanishes because of the systematic use of third-party information. These results are obtained both in simple reduced-form regressions and in a data-calibrated state-of-the-art model.
Keywords: D82; H26; K42; 330; Steuerflucht; Steuertarif; Asymmetrische Information; Steuerfahndung; Regression; Dänemark